O mercado internacional de equipamentos militares: Negócios e política externa - Rodrigo Fracalossi de Moraes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The purpose of this paper is to identify whether international transfers of military equipment are predominantly motivated by economic or political reasons. Eight countries were selected to be individually analyzed: the USA, Russia, France, the UK, Germany, Sweden, Switzerland and Japan. Although all of them consider both political and economic dimensions on their decisions to supply military equipment, the predominance of one of these dimensions - or the balance between them - can be identified for each country. Then they were separated into three groups: the USA, Sweden and Japan, which emphasize the political dimension; France, the UK and Russia, which give more importance to the economic dimension; and Switzerland and Germany, who which consider both dimensions equally important. The analysis concludes that the eight countries consider both dimensions in their decisions, even though in six cases there is a predominance of one of them. The reasons for the prioritization of the political or the economic aspects, however, are different for each country.
Keywords: F52; 330